2020
DOI: 10.1093/texcom/tgaa067
|View full text |Cite
|
Sign up to set email alerts
|

Identification of White Matter Networks Engaged in Object (Face) Recognition Showing Differential Responses to Modulated Stimulus Strength

Abstract: Blood oxygenation level-dependent (BOLD) signals in magnetic resonance imaging (MRI) indirectly reflect neural activity in cortex, but they are also detectable in white matter (WM). BOLD signals in WM exhibit strong correlations with those in gray matter (GM) in a resting state, but their interpretation and relationship to GM activity in a task are unclear. We performed a parametric visual object recognition task designed to modulate the BOLD signal response in GM regions engaged in higher order visual process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…However, the sensitivity of detecting WM activation is often much lower compared to GM, possibly due to incorrect assumptions made about the time courses of responses that are incorporated into regression models for detection 16 . According to our recent studies, WM tracts that are involved in the processing of external stimuli may exhibit distinct time courses different from GM, with reduced magnitudes and delayed peaks, reflecting quantitative differences in hemodynamic conditions between GM and WM [17][18][19] . These findings highlight the importance of characterizing the temporal profiles of BOLD signals so that neurovascular coupling in WM may be better understood and incorporated appropriately into analyses.…”
Section: Introductionmentioning
confidence: 93%
“…However, the sensitivity of detecting WM activation is often much lower compared to GM, possibly due to incorrect assumptions made about the time courses of responses that are incorporated into regression models for detection 16 . According to our recent studies, WM tracts that are involved in the processing of external stimuli may exhibit distinct time courses different from GM, with reduced magnitudes and delayed peaks, reflecting quantitative differences in hemodynamic conditions between GM and WM [17][18][19] . These findings highlight the importance of characterizing the temporal profiles of BOLD signals so that neurovascular coupling in WM may be better understood and incorporated appropriately into analyses.…”
Section: Introductionmentioning
confidence: 93%
“…WM BOLD activity can be evoked by stimulation in task-specific tracts or regions. The magnitude of WM signals in a task reflects those in GM engaged in the same task, and may be modulated by the same factors [15][16]. At rest, WM tracts show reproducible patterns of connectivity which are summarized in Functional Connectivity Matrices (FCMs) obtained by analyzing resting state correlations between segmented WM and GM parcellations [17]; the FCM relating WM to GM is altered in various pathologies including Alzheimer’s disease in a manner that correlates with behavioral measures [18].…”
Section: Introductionmentioning
confidence: 99%
“…While reports of BOLD signals in gray matter (GM) have dominated the fMRI literature, there have been far fewer descriptions of BOLD effects in white matter (WM), partly because they are weaker due to the smaller blood flow/volume compared to GM ( Helenius et al, 2003 ). However, a growing body of evidence suggests that BOLD signals can be reliably detected in WM and reflect neural activities ( Courtemanche et al, 2018 ; D’Arcy et al, 2006 ; Ding et al, 2018 ; Fraser et al, 2012 ; Gawryluk et al, 2014 ; Gore et al, 2019 ; Li et al, 2020a , 2020b ; Mishra et al, 2020 ; Peer et al, 2017 ; Schilling et al, 2019 ; Wu et al, 2019 ), and such signals are altered significantly in patients with neurological or psychiatric disorders ( Gao et al, 2020 ; Huang et al, 2020 ; (Lin et al, 2020); (Lin et al, 2020). Recent studies have demonstrated how the temporal profiles of WM BOLD responses to stimuli are different from GM, with reduced magnitudes and delayed peaks, reflecting differences in hemodynamic conditions between GM and WM ( Fraser et al, 2012 ; Li et al, 2019 ; Tong et al, 2017 , 2013 ; Wang et al, 2020 ; Yarkoni et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%